Disparities in Regional Development in West Nusa Tenggara: An Economic Analysis of Districts and Cities 2018–2022 - Fitri, Arina Nur; Rindiani, Sherly Senja (University Merdeka Malang, 2024)
This study aims to analyze the economic structure and regional development disparities across districts and cities in West Nusa Tenggara (NTB) from 2018 to 2022. The research employs the Williamson Index, Klassen Typology, Location Quotient (LQ), and Shift-Share analysis methods to evaluate economic imbalances. The findings reveal that regional economic disparities in NTB are significantly high, as indicated by the Williamson Index nearing 1. Additionally, the Klassen Typology results demonstrate notable inequality in economic growth. Sectoral analysis using the LQ and Shift-Share methods highlights differences in regional economic performance, influenced by the characteristics of each analytical tool. The study suggests that the NTB government should formulate targeted strategies to maximize the potential of key economic sectors in order to achieve higher economic growth and balanced regional development.